2008
DOI: 10.1155/2008/763706
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Synthesizing Black Birnessite Nanoparticles: From Brown to Black Birnessite with Nanostructures

Abstract: A new method for preparing black birnessite nanoparticles is introduced. The initial synthesis process resembles the classical McKenzie method of preparing brown birnessite except for slower cooling and closing the system from the ambient air. Subsequent process, including wet-aging at7∘Cfor 48 hours, overnight freezing, and lyophilization, is shown to convert the brown birnessite into black birnessite with complex nanomorphology with folded sheets and spirals. Characterization of the product is performed by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…7. The TEM image shows aggregates of dark, fibrous minerals, similar in morphology to Mn oxides studied previously (Cheney et al, 2008). Also in the figure, EDS elemental spectra confirms that these dark fibrous particles are predominately Mn and O.…”
Section: Mn Oxidation and Reduction: Evidence From Water Column Partisupporting
confidence: 78%
See 1 more Smart Citation
“…7. The TEM image shows aggregates of dark, fibrous minerals, similar in morphology to Mn oxides studied previously (Cheney et al, 2008). Also in the figure, EDS elemental spectra confirms that these dark fibrous particles are predominately Mn and O.…”
Section: Mn Oxidation and Reduction: Evidence From Water Column Partisupporting
confidence: 78%
“…Recalculating Mn oxidation rates based only on the first two time points for 119-121 m gives higher rates of 0.36-0.72 µmol l −1 d −1 . Aggregates of dark, fibrous minerals seen in the TEM image are similar in morphology to birnessite (Cheney et al, 2008), and an EDS spectrum collected from the point indicated with red crosshairs shows predominately Mn and O present.…”
Section: Oxidation Of Mnmentioning
confidence: 78%
“…NMO was obtained under fume cupboard, by the reduction of KMnO 4 (200 mL, 0.02 mol L −1 ), with HCl (5 mL, 4.0 mol L −1 ) as described in the literature (Chen et al 2011;Cheney et al 2008). The process is described by the following reaction:…”
Section: Synthesis Of Nmomentioning
confidence: 99%
“…The activity concentration of 137 Cs was calculated for each sample using the following equation (Cheney et al 2008;IAEA 2004):…”
Section: Characterization Of Nmomentioning
confidence: 99%
“…MnO2 which are well known as a strong adsorbents of metal ions, is naturally found in soils, aquifers and sediment, and therefore cost-effective. In addition, MnO2 can be synthesized using oxidation of Mn(II) in basic solution [19], oxidation by MnO4 - [20], O2, K2S2O8, and H2O2 [21], or reduction of MnO4using different routes [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%